2015
DOI: 10.1093/mnras/stv1207
|View full text |Cite
|
Sign up to set email alerts
|

TheSuzakuview of highly ionized outflows in AGN – II. Location, energetics and scalings with bolometric luminosity

Abstract: Ongoing studies with XMM-Newton have shown that powerful accretion disc winds, as revealed through highly-ionised Fe K-shell absorption at E 6.7 keV, are present in a significant fraction of Active Galactic Nuclei (AGN) in the local Universe (Tombesi et al. 2010a). In Gofford et al. (2013) we analysed a sample of 51 Suzaku-observed AGN and independently detected Fe K absorption in ∼ 40% of the sample, and we measured the properties of the absorbing gas. In this work we build upon these results to consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
201
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 164 publications
(233 citation statements)
references
References 77 publications
28
201
0
Order By: Relevance
“…Thus the observed velocities can be easily reproduced within this framework. Note that a comparable positive cor-relation between the outflow velocity and luminosity has been recently found by Gofford et al (2015) and Fiore et al (2017), the latter from collating a sample of known AGN outflows.…”
Section: A Radiatively Driven Wind?supporting
confidence: 74%
“…Thus the observed velocities can be easily reproduced within this framework. Note that a comparable positive cor-relation between the outflow velocity and luminosity has been recently found by Gofford et al (2015) and Fiore et al (2017), the latter from collating a sample of known AGN outflows.…”
Section: A Radiatively Driven Wind?supporting
confidence: 74%
“…Often, the implied velocity is very high, up to the mildly relativistic values of v out ;0.1 c for the so-called ultra-fast outflows (UFOs; e.g., Tombesi et al 2010Tombesi et al , 2011Tombesi et al , 2014Tombesi et al , 2015Gofford et al 2013;Longinotti et al 2015;Nardini et al 2015;Parker et al 2017). These winds are observable at sub-parsec scales from the central black hole, consistently with an accretion disk interpretation, and they seem to be powerful enough to have a substantial effect on the host galaxy environment (e.g., Tombesi et al 2012, Wagner et al 2013Gofford et al 2015;Nardini et al 2015).…”
Section: Introductionsupporting
confidence: 58%
“…A UFO with velocity v out ;0.15c was detected in 3C390.3 (Tombesi et al 2010bGofford et al 2013Gofford et al , 2015. The lower and upper limits on the distance, mass outflow rate, and mechanical power are d;0.002-0.02 pc,…”
Section: Warm Absorbermentioning
confidence: 93%
“…The detection of WAs was reported in 3C382, 3C445, 3C390.3, and 4C+74.26 (Ballantyne 2005;Reeves et al 2009Reeves et al , 2010Torresi et al 2010Torresi et al , 2012. Moreover, UFOs have been reported in 3C111, 3C120, 3C390.3, 3C445, 4C +74.26, and Cygnus A (Tombesi et al 2010bBallo et al 2011;Braito et al 2011;Gofford et al 2013Gofford et al , 2015Reynolds et al 2015). A recent X-ray study of a sample of 26 radio galaxies reported that the frequency of UFOs is likely in the interval f; 50% ± 20% .…”
Section: Introductionmentioning
confidence: 96%